Mekanisme Pemotongan dan Pelaporan PPh Pasal 23 atas Jasa Penyediaan Tenaga Kerja pada CV. ABC - Diva Meilani Putri (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
Tax is one of the sources of government revenue that play a role in financing national development. The reform of Indonesia’s tax system from DJP Online to coretax requires taxpayers to adapt to the new system. CV. ABC is a manufacturer of polyurethane products with its main product being bus seat foam (foam for bus passenger seats) that uses a ousourcing services to clean its entire production area. In connection with the use of these services, CV. ABC is obligated to withhold and report income tax under Article 23 in accordance with applicable tax regulations. This final project report aims to examine the mechanism for withholding and reporting income tax under Article 23 on outsourcing services at CV. ABC through the coretax system. The data used includes both quantitative and qualitative data. The data sources used are primary and secondary data, collected through observation, interviews, literature review, and documentation. The results of the Practical Work Experience (PKN) indicate that withholding of Income Tax Article 23 is conducted via e-Bupot feature on the coretax system at a rate of 2% of the gross management fee. Subsequently, payment and reporting are carried out through the Unified Periodic Income Tax Return (SPT Masa PPh Unifikasi) until an Electronic Receipt (BPE) is obtained. Additionally, the outsourcing services are subject to Value-Added Tax (VAT) under the Other Values scheme, which is collected by PT. XYZ as the service provider and can be credited as Input Tax by CV. ABC.
finalisasi 20 Juli 2026_Yudi
Keywords: Tax; Income Tax 23; Outsourcing Services; Withholding and Reporting